Bibliometric analysis and systematic literature review of the intelligent tutoring systems - Cuéllar-Rojas, Oscar-Andrés; Hincapié-Montoya, Mauricio; Contero, Manuel; Güemes-Castorena, David (Frontiers in Education, 2022)
This article is a literature review, having as a central axis the educational evaluation mediated by Intelligent Tutoring Systems (ITS seeking to establish state of the art on the implementations executed in the last 20 years and their impact on the evaluation process. The PRISMA methodology was applied for the literature review; the inclusion criteria were conducted using R software and bibliometric techniques with a general search equation that allowed access to all ITS production in Scopus. Subsequently, with the help of artificial intelligence, text mining was used to identify topics of interest in the scientific community, followed by further filtering. Finally, the selected full texts were analyzed with NVIVO software extracting emerging challenges in the field, obtaining 163 full texts for analysis. Among the main findings, the primary purpose of evaluation in ITS was summative, peer and self-evaluation did not have the same level of importance as hetero evaluation, and ITS focus was quantitative. All this allowed us to conclude that the analyzed texts did not implement a holistic perspective and therefore evidenced the need to establish a framework for constructing an ITS using current technologies that integrate the mentioned variables.